2014
DOI: 10.3892/ijmm.2014.1751
|View full text |Cite
|
Sign up to set email alerts
|

Targeting endothelin receptors A and B attenuates the inflammatory response and improves locomotor function following spinal cord injury in mice

Abstract: After spinal cord injury (SCI), the disruption of blood-spinal cord barrier by activation of the endothelin (ET) system is a critical event leading to leukocyte infiltration, inflammatory response and oxidative stress, contributing to neurological disability. In the present study, we showed that blockade of ET receptor A (ETAR) and/or ET receptor B (ETBR) prevented early inflammatory responses directly via the inhibition of neutrophil and monocyte diapedesis and inflammatory mediator production following traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Post-SCI oxidative stress damages the ion steady state inside and outside the mitochondrial membrane, Ca 2+ accumulates inside the mitochondria, causing mitochondrial damage and aerobic energy metabolic disorders and inhibiting the synthesis of ATP (4). Following SCI, excessive activity of free radicals may be applied to the postsynaptic neuron, activating nearby astrocytes and microglia, causing ionic imbalance at the neuronal cell membrane (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-SCI oxidative stress damages the ion steady state inside and outside the mitochondrial membrane, Ca 2+ accumulates inside the mitochondria, causing mitochondrial damage and aerobic energy metabolic disorders and inhibiting the synthesis of ATP (4). Following SCI, excessive activity of free radicals may be applied to the postsynaptic neuron, activating nearby astrocytes and microglia, causing ionic imbalance at the neuronal cell membrane (21).…”
Section: Discussionmentioning
confidence: 99%
“…The former consists of instantaneous mechanical damage that is reversible. Secondary damage gradually forms in the weeks following primary damage, and is accompanied by a series of cell metabolism and gene expression changes, including excitatory amino acid release, free radical damage, decrease in ion inflow, inflammation and cell apoptosis, resulting in more harm than primary damage (4,5). Numerous studies have shown that post changes of SCI gene expression play an important role in the pathological process (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The spinal cord water content was assessed by the following equation: [(wet weight -dry weight)/wet weight] ×100% (8). …”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, therapeutic strategies that employ ET-1 antagonists to impede ET-1-mediated vasoconstriction are beneficial in terminating SCI progression. ET receptor antagonists likewise prevent or delay axonal degeneration after SCI [149], and blockade of ET A R and/or ET B R reduces inflammatory responses and oxidative stress, overturns MMP-9 activation, and enhances long-term neurological function post-injury [151]. Following spinal cord trauma, vascular ET A R/ET B R activation plays a critical role in post-traumatic ischemia, whereas astrocyte-only ET B R activation is associated with reactive gliosis [143].…”
Section: Endothelinsmentioning
confidence: 99%